The dragon in the sea - Klimo, Kate (Dragon keepers ;, 2012)
Jesse and Daisy and their dragon friend, Emmy, try to recover a Thunder Egg from merpeople who stole it from Daisy near the Inn of the Barking Seal, where the cousins are visiting their grandmother Polly.